INNOVATION ORIENTATION AND EXCELLENCE COMPETE AS PERFORMANCE DETERMINANT COMPONENTS: ANTECEDENTS ORIENTATION VARIABLE OF ENTREPRENEURSHIP AND LEARNING - Darmanto Darmanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
This study aims to provide information about the conceptual controversy regarding Orientation of Innovation and Competitive Advantage as Performance Determinant Components: Entrepreneurial and Entrepreneurial Antecedents Variables. The population of this research is the owner, manager and / or batik business employees in Batik Kauman village, Laweyan. The purpose sampling method was used and determined 100 samples. Motivation analysis used is Structural Equation Modeling (SEM) analysis with Lisrel software.The results of this study states that the orientation of innovation and competitive advantage had a positive and significant effect on performance. Entrepreneurship and Learning positively and significantly influence on innovation orientation and competitive advantage. Keywords : Innovation Orientation, Competitive Advantage, Entrepreneurship, Learning, Performance